An Efficient Nonviral Method to Generate Integration‐Free Human‐Induced Pluripotent Stem Cells from Cord Blood and Peripheral Blood Cells123. (25th February 2013) - Okita, Keisuke; Yamakawa, Tatsuya; Matsumura, Yasuko; Sato, Yoshiko; Amano, Naoki; Watanabe, Akira; Goshima, Naoki; Yamanaka, Shinya
Abstract The generation of induced pluripotent stem cells (iPSCs) provides the opportunity to use patient‐specific somatic cells, which are a valuable source for disease modeling and drug discovery. To promote research involving these cells, it is important to make iPSCs from easily accessible and less invasive tissues, like blood. We have recently reported the efficient generation of human iPSCs from adult fibroblasts using a combination of plasmids encoding OCT3/4, SOX2, KLF4, L‐MYC, LIN28, and shRNA for TP53. We herein report a modified protocol enabling efficient iPSC induction from CD34+ cord blood cells and from peripheral blood isolated from healthy donors using these plasmid vectors. The original plasmid mixture could induce iPSCs; however, the efficiency was low. The addition of EBNA1, an essential factor for episomal amplification of the vectors, by an extra plasmid greatly increased the efficiency of iPSC induction, especially when the induction was performed from αβT cells. This improvement enabled the establishment of blood‐derived iPSCs from seven healthy donors ranging in age from their 20s to their 60s. This induction method will be useful for the derivation of patient‐specific integration‐free iPSCs and would also be applicable to the generation of clinical‐grade iPSCs in the future. STEM CELLS2013;31:458–466